Pengaruh Multimedia Pembelajaran Interaktif PKK dalam Meningkatkan Kreativitas Berwirausaha Siswa SMK Negeri 2 Solok - Ahmad Ridwan; Waskito; Rizky Ema Wulansari; Sri Rizki Putri Primandari (TSAQOFAH, 2026)
Although the use of interactive multimedia in entrepreneurship education has been widely studied, empirical evidence regarding its effect on the entrepreneurial creativity of Mechanical Engineering students at SMK Negeri 2 Solok remains limited. This study aimed to analyze the effect of interactive learning multimedia in the Creative Products and Entrepreneurship subject on students’ entrepreneurial creativity. The study employed a quantitative approach with a post-test-only control group quasi-experimental design. The study population consisted of 68 Grade XI Mechanical Engineering students, with 19 students involved in instrument testing and 49 students included in the study sample, comprising 25 students in the experimental class and 24 students in the control class. Data were collected through questionnaires, observation, and documentation. The final instrument consisted of 28 valid items with a Cronbach’s alpha coefficient of 0.978. The data were analyzed using normality tests, a homogeneity test, and an independent-samples t-test. The results showed that the mean entrepreneurial creativity score of students in the experimental class was 89.52, which was higher than the control class score of 72.54. The hypothesis-testing results indicated a significant difference between the two groups (t = 16.489; p < 0.001). These findings confirm that the use of interactive learning multimedia has a positive effect on students’ entrepreneurial creativity and supports the development of more contextual entrepreneurship learning in vocational education. Schools and Creative Products and Entrepreneurship teachers need to systematically integrate interactive multimedia, while future studies need to involve more schools and apply project-based assessment.